2021
DOI: 10.3390/metabo12010027
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Signatures for the Effects of Weight Loss Interventions on Severe Obesity in Children and Adolescents

Abstract: Childhood obesity has increased worldwide, and many clinical and public interventions have attempted to reduce morbidity. We aimed to determine the metabolomic signatures associated with weight control interventions in children with obesity. Forty children from the “Intervention for Children and Adolescent Obesity via Activity and Nutrition (ICAAN)” cohort were selected according to intervention responses. Based on changes in body mass index z-scores, 20 were responders and the remaining non-responders. Their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 41 publications
(44 reference statements)
1
11
0
Order By: Relevance
“…To the best of our knowledge, few interventional studies have investigated the reversibility of the metabolomic signature that characterizes childhood obesity [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. For instance, while one work did not detect any difference in the serum amino acid profile among children with obesity, measured before and after a 48-week exercise-based program [ 18 ], in a 1-year lifestyle intervention administered to a cohort of children with obesity, 17 metabolites were reported to be predictive of weight loss, including arginine, 1 lysophosphatidylcholine (LysPC a C18:0) and 15 long-chain and unsaturated phosphatidylcholines (13 diacyl and 2 acyl-alky PCs) [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, few interventional studies have investigated the reversibility of the metabolomic signature that characterizes childhood obesity [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. For instance, while one work did not detect any difference in the serum amino acid profile among children with obesity, measured before and after a 48-week exercise-based program [ 18 ], in a 1-year lifestyle intervention administered to a cohort of children with obesity, 17 metabolites were reported to be predictive of weight loss, including arginine, 1 lysophosphatidylcholine (LysPC a C18:0) and 15 long-chain and unsaturated phosphatidylcholines (13 diacyl and 2 acyl-alky PCs) [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, while one work did not detect any difference in the serum amino acid profile among children with obesity, measured before and after a 48-week exercise-based program [ 18 ], in a 1-year lifestyle intervention administered to a cohort of children with obesity, 17 metabolites were reported to be predictive of weight loss, including arginine, 1 lysophosphatidylcholine (LysPC a C18:0) and 15 long-chain and unsaturated phosphatidylcholines (13 diacyl and 2 acyl-alky PCs) [ 15 ]. In a more recent 18-month weight loss intervention in a pediatric population, a cluster of 13 metabolites was identified to change at the end of the study, denoting the involvement of urea and tricarboxylic acid (TCA) cycles and several amino acid metabolic pathways (i.e., arginine, glutamine, glutamate, cysteine, and methionine) [ 19 ]. One limitation of these (even) long-lasting studies is the adoption of an out-patient setting, i.e., the enrolment of participants that followed physician-imparted instructions of lifestyle change at home, without the medical supervision that, instead, is ensured in an in-patient setting.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been established that these mechanisms are impaired in patients with obesity [ 49 ]. For instance, Sohn and colleagues demonstrated that TCA metabolites were higher in children affected by obesity before 18 months of weight loss [ 50 ]. The catabolism of branched-chain amino acids (BCCAs) seems to play a central role in all the lipid and energetic pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Such science, therefore, has the potential to aid decision making in the field of personalized medicine [ 88 , 89 , 90 ]. Therefore, the identification of possible biomarkers in pediatric populations via metabolomics could provide an opportunity not only to better characterize this condition, but also to find new and more effective prevention and treatment approaches [ 91 ], allowing for tailor-made management [ 85 , 92 ]. The close correlation between microbiota and metabolomic analysis is schematized in Figure 1 .…”
Section: Metabolomics In Childhood Obesitymentioning
confidence: 99%